SUSTAINABLE ENGINEERING EDUCATION EMBEDDED CURRICULA RESEARCH PROJECT - Alfredo Soeiro (2023)
The SEFI Annual Conference is a scientific conference focused on Engineering Education and the biggest event of this type in Europe. SEFI Annual Conferences are a unique opportunity for professors, students, industry and profesional organisations to exchange their views and to meet their peers and create a European network of contacts. The topics of the conferences reflect the objectives of the society and the priorities identified by its members. The flagship European conference for engineering education is the annual conference of the European Society for Engineering Education (SEFI). Companies and organisations with an interest in engineering education are invited to support the 2023 SEFI Annual Conference. The theme for the conference will be Engineering Education for Sustainability